2015
DOI: 10.1155/2015/840640
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Receptor Signals as Prognosticators for Urothelial Tumor

Abstract: There is a substantial amount of preclinical or clinical evidence suggesting that steroid hormone receptor-mediated signals play a critical role in urothelial tumorigenesis and tumor progression. These receptors include androgen receptor, estrogen receptors, glucocorticoid receptor, progesterone receptor, vitamin D receptor, retinoid receptors, peroxisome proliferator-activated receptors, and others including orphan receptors. In particular, studies using urothelial cancer tissue specimens have demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 113 publications
(157 reference statements)
2
23
0
Order By: Relevance
“…It has been shown that the levels of AR expression are significantly lower in bladder tumors than in non-neoplastic urothelial tissues as well as in high-grade/muscle-invasive bladder carcinomas than in low-grade/superficial tumors [21, 22]. Nonetheless, AR positivity in bladder tumors, especially in muscle-invasive carcinomas, has been associated with worse patient outcomes [8, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the levels of AR expression are significantly lower in bladder tumors than in non-neoplastic urothelial tissues as well as in high-grade/muscle-invasive bladder carcinomas than in low-grade/superficial tumors [21, 22]. Nonetheless, AR positivity in bladder tumors, especially in muscle-invasive carcinomas, has been associated with worse patient outcomes [8, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective cohort studies have also revealed that androgen deprivation therapy (ADT) which has been widely used for the treatment of prostate cancer prevents the development of de novo [19] and recurrent [20] bladder tumors in male patients. Immunohistochemical studies in bladder cancer specimens have further indicated correlations between AR expression and disease progression, while no significant difference in its levels between male and female tumors has been found [21, 22]. Of note, androgen was recently shown to reduce sensitivity of AR-positive bladder cancer cells to doxorubicin [23], an anthracycline anti-tumor antibiotic often used for intravesical chemotherapy to prevent tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is therefore assumed that the disparities in the levels of circulating sex hormones and the systemic hormonal milieu lead to differential activation of, for instance, AR and ERs, in male vs. female urothelial cells. We observed that the positive rates of AR and PR tended to be higher in male and female UUTUCs, respectively.…”
Section: Ar Positivitymentioning
confidence: 99%
“…5,9 In particular, androgens, estrogens, and glucocorticoids have been shown to modulate tumor outgrowth in a variety of cell line and animal models. Accordingly, in these preclinical models, treatment with clinically available drugs, including AR antagonists or inhibitors being used in prostate cancer patients, ER modulators being used in breast cancer patients (or estrogens), or glucocorticoids being used as anti-inflammatory, anti-immune, or anti-tumor agents, resulted in inhibition of cell proliferation and invasion in urothelial tumor lines as well as tumor development and growth in animals.…”
Section: Ar Positivitymentioning
confidence: 99%
See 1 more Smart Citation